7z-6z+8-8=6z+14-8

Simple and best practice solution for 7z-6z+8-8=6z+14-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7z-6z+8-8=6z+14-8 equation:



7z-6z+8-8=6z+14-8
We move all terms to the left:
7z-6z+8-8-(6z+14-8)=0
We add all the numbers together, and all the variables
7z-6z-(6z+6)+8-8=0
We add all the numbers together, and all the variables
z-(6z+6)=0
We get rid of parentheses
z-6z-6=0
We add all the numbers together, and all the variables
-5z-6=0
We move all terms containing z to the left, all other terms to the right
-5z=6
z=6/-5
z=-1+1/5

See similar equations:

| 5/11=y/4 | | 8a+36=6a-14 | | 2x^=288 | | 3/4w-1/2w=16 | | 2+7x+4x=57 | | |-7-7x|=14 | | x+2x+(2x-24)=180 | | 10.2x+24.59=-9.8x+22.93 | | 2x+9-4x=27 | | 54=2x+7x+9 | | 33p+16=18 | | 6.4x=19 | | 2+5x+5x=62 | | 2x/24=(x+1)/9 | | 6b-30=11b | | r/2+5=7 | | x+27=2x+27 | | 4-160y=24 | | 2w-3=24 | | 6x-9x-4=2x-4 | | -5x-7=53 | | 5(x+1)=3(x−1) | | 126-36n=2n+7 | | -4(5n+1)=0 | | -4(3x+2)=-80 | | 3m^2+240=0 | | 30x-6=14 | | 6y-4y=-20 | | 2/3(6j+9(=3j+7 | | 4/5x-7=37 | | -5.6+-5c+3c^2=0 | | 12(2x+3)+12(x-3)=3(x^2-9) |

Equations solver categories